Alan Turing and his contemporaries : building the world's first computers - Lavington, Simon (British Informatics Society Ltd., 2012)
Secret wartime projects in areas such as code-breaking, radar and ballistics produced a wealth of ideas and technologies that kick-started the development of digital computers. This is the story of the people and projects that flourished in the post-war period. Their influence is still discernable deep down within today's hardware and software.